Asymptomatic bilateral common iliac artery dissections in previously undiagnosed vascular Ehlers-Danlos syndrome - Lavoie, Matthew (BMJ Case Rep, 2019)
We report a case of a 35-year-old woman found to have vascular Ehlers-Danlos syndrome (vEDS) after family history of sudden death due to aortic dissection in her otherwise healthy brother prompted further imaging workup and consideration of an underlying heritable genetic condition. CT angiogram of the aorta with intravenous contrast revealed an abdominal aortic artery dissection below the level of the renal arteries extending from the bifurcation into the left common iliac artery with an additional focal dissection of the right common iliac artery. To the author’s knowledge, this is the first report of asymptomatic bilateral common iliac artery dissections as a part of the initial presentation of a patient with underlying vEDS. Additionally, this case highlights the importance of familial diagnostic screening in inherited vasculopathies. Clinical history, genetic testing and management are discussed.